2021
DOI: 10.14512/gaia.30.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Intended and unintended effects of statutory deposit return schemes for single-use plastic bottles: Lessons learned from the German experience

Abstract: Several EU countries discuss introducing deposit systems for single-use bottles to mitigate pollution. However, as an analysis of the German experiences indicates, the introduction of a deposit on single-use beverage containers might unintendedly compromise the endeavor to implement a circular economy. Such unintended effects need to be considered to enable the implementation of a circular economy that prioritizes reduction and reuse compared to recycling.High levels of environmental pollution and low recycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Rhein and Sträter 27 present experiences from using single‐ and multi‐use deposit systems and discuss what lessons can be used by others. Šuškevičé and Kruopiené 28 assess the environmental benefits of cup reuse models in open summer festivals on material circularity and the avoidance of disposable plastic.…”
Section: Sustainability and Circular Economymentioning
confidence: 99%
“…Rhein and Sträter 27 present experiences from using single‐ and multi‐use deposit systems and discuss what lessons can be used by others. Šuškevičé and Kruopiené 28 assess the environmental benefits of cup reuse models in open summer festivals on material circularity and the avoidance of disposable plastic.…”
Section: Sustainability and Circular Economymentioning
confidence: 99%
“…• an analysis of the effects of a deposit system implemented in Germany indicated that the return rate of single-use PET bottles has increased to around 96% in 2018 (Rhein & Sträter, 2021), • OECD reports:…”
Section: Introductionmentioning
confidence: 99%
“…Additional case of implementing DRS systems is described in the work of Linderhof [14], who simulated the impacts of DRS implementation on the recycling rate of small electronic appliances and batteries, stating that the DRS is especially effective in cases where current recycling rates are relatively low. Rhein [15] discussed the effects of DRS systems on the overall adverse effectiveness of the circular economy in Germany, stating the increased level of recycling means reduction and reuse on the product level. A case study and economic analysis was performed by [16] on the conditions of the first DRS implementation in Croatia, calculating the overall system costs and identifying the main economic drivers.…”
Section: Introductionmentioning
confidence: 99%